DIGITAL TECHNOLOGY AS SUPPORT OF COGNITIVE PROCESSES OF PEOPLE WITH VISUAL IMPAIRMENTS - Spinarova, Gabriela; Vachalova, Veronika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
At present, we increasingly encounter the concept of so-called digital literacy. Digital technologies are constantly evolving in this field and play an important role in human life. They are important not only in the labor market but also in education and human skills development. Digital technologies are thus one of the means by which we can develop the cognitive processes of visually impaired people. We can thus help them to improve a number of areas that are limited due to loss or reduction of visual perception. Especially, thinking, memory, and creating ideas are very important. This contribution was created within the solution of the project TAČR – Reduction of information deficit and development of the imagination of visually impaired people through 3D models with auditory elements in cooperation with the project PIGŽU – Support of information literacy of pupils and teachers. The first of the projects aims to reduce the information deficit caused by the loss or reduction of visual perception in visually impaired people using multisensory action. At the same time, it aims to develop their spatial imagination. The second project then focus on the creation of digital aids, which aims primarily at the development and support of computational thinking. In addition to mainstream primary school pupils, the project also focuses on pupils with special educational needs, including visually impaired individuals. The main output of the project is the creation of aids, including methodologies, using digital technologies. These are technologies such as Ozobot, Blue-Bot, or Bee-bot. The aim of the paper is to acquaint with the project, to provide at least basic information about digital technologies, and especially to describe the possibilities of personality development, skills, and abilities using these technologies in visually impaired students.